Dano moral ambiental coletivo na sociedade de risco: estudo sobre a instalação de uma empresa de agronegócio no município de Santarém- Pará - Pinto, Celciane Malcher (2016)
Before the environmental crisis scenario there is the theory of Ulrich Beck venturecompany dealing with brand new environmental risks characterized by being unpredictable and uncontrollable resulting from the current model of modernity which, in turn, requires new thinking about science and Own environmental law as to their role in this society. In this context, the present study aims to investigate the recognition of off-balance sheet damage (moral) collective environment is a civilian accountability mechanism adapted to the profile of new risks, since repair is in accordance with the principle of full repairability. We adopted the method of deductive approach using case study and as indirect documentation to literature through books, journals and virtual vehicles related to the theme and the Civil Public Inquiry organized by the MPF on the case study. For this, initially the research, pursuing a multidisciplinary approach, presents the contours of qualifying company at risk in Ulrich Beck's vision and discusses the challenges of environmental law at thisjuncture. This study also presents some considerations relating to liability, the study of environmental damage and new paradigms of environmental liability. Then, far-there will be a doctrinal analysis, case law and legislation the Supreme Court on the environmental collective moral damage which currently judged fully admit their occurrence before accepted only in relation to individual moral aspect. For this study is taken against the backdrop of the possible occurrence of such damage mode for setting up and Cargill's activities in Santarém-PA, a situation that caused various environmental problems particularly regarding the degradation of cultural heritage with the suppression of beach Vera Paz and ground the archaeological site Tapajó, bringing with it the loss of the population's quality of life. Thus, it is concluded that a new hermeneutics which brings together environmental principles and allows for accountability for collective environmental moral damage there is the addition of new instrument in the search for adaptation to the new profile of environmental risks through an ever repair more integral.